JURIDICAL REVIEW IN DETERMINING THE HEIR AND THE AMOUNT OF EACH SHARE BASED ON THE WESTERN INHERITANCE LEGAL SYSTEM - Heri Purnomo (UNTAG Law Review, 2022)
Inheritance law is currently a question that is widely questioned among the public, considering that there are still many people who do not realize the importance of inheritance law or may not know and understand how inheritance issues must be resolved. Not infrequently when heirs have to share inheritance, disputes arise that don't need to happen, if each party can realize and understand the applicable inheritance law. Starting from the background above, the author is interested in raising inheritance law, especially related to western inheritance law. the question of how to determine the heirs and how to determine the share/potie of each of the heirs. The western inheritance law system regulates how to determine heirs either based on blood relations or because of a will, but given the breadth of inheritance issues, in this paper, the author limits the determination and share of each heir, when the heir does not leave a will.